Double-Blind Randomized Trial on the Efficacy in a Short-Time Follow-Up of the “Quick Liberatory Rotation” Maneuver in Treating Posterior Canal BPPV - Califano, Luigi; Salafia, Francesca; Mazzone, Salvatore; Grazia Melillo, Maria; Califano, Maria (Journal of Otolaryngology Advances, 2014)
This double-blind randomized studyevaluates the efficiency of the Quick Liberatory Rotation maneuver (QLR) in solving signs and symptoms of Posterior Canal BPPV in a short time follow-up comparing the efficiency of QLR vs. a sham maneuver (“Fake QLR”).The study was performed at an input-output tertiary center for balance disorders.From January to September 2012, 200 patients with signs and symptoms of Posterior Canal BPPV respected the inclusion criteria in the study. The diagnosis was based on observation with binocular infrared videonystagmoscopy of the paroxysmal torsional and upbeat nystagmus evoked through the Dix-Hallpike test (DHT). Patients were divided in two groups, 100 in the group treated by QLR (Group 1) and 100 in the control group treated by “Fake QLR” (Group 2). Before the treatment, they self-evaluated a Visual Analogue Score on their vertiginous complaints (V-VAS). Patients were controlled one hour after the treatment by a blinded examiner about the first phase of the study through DHT, the Straight head-hanging positioning test and the Head Roll test in supine position and assessed again with V-VAS. Patients with a persisting positive Dix- Hallpike test were subsequently treated through QLR. The main outcome measure is the number of patients treated through QLR or “Fake QLR” with a negative DHT one hour after the first treatment. At the post-procedure check, 79 patients from Group 1 presented a negative DHT with little or no subjective symptoms, whereas all the patients of Group 2 presented persistence of a positive DHT. The presence of the secondary nystagmus during QLR (“liberatory” nystagmus) was significantly correlated with a negative DHT at the post-procedure control. In Group 1 pre- and post-treatment V-VAS differences were significant; post-treatment V-VAS differences were significant in Group 1 vs. Group 2. In a short time follow-up QLRis an effective treatmentfor Posterior Canal BPPV when compared to a sham maneuver.
Keywords: Posterior canal BPPV; Quick Liberatory Rotation maneuver; Canalolithiasis; BPPV therapy